Control Interno En La Gestión De Inventarios De La Empresa Construmotion S.A., Año 2023 - Constantine Almachi, Doménica Ismaela (2025)
The main objective of this research was to analyze the impact of internal control in the inventory management of construction projects developed by Construmotion S.A. during the year 2023 in order to identify current inventory control practices and evaluate their impact on operating costs, execution times and profits of the projects. The research methodology had a mixed approach (quantitative and qualitative) where structured surveys were applied to the personnel in charge of the projects, in addition, an interview was conducted with the operational manager to understand the challenges and opportunities for improvement in the processes. A documentary analysis of inventory records and an internal control assessment were also conducted to determine the direct impact on profitability. The data collected was processed using statistical tools such as Excel. Relevant aspects regarding inventory control and deficiencies in control policies were revealed, and the implementation of a more efficient inventory system was proposed as an improvement strategy to achieve optimization in the management of resources so that the company can maintain good profitability margins and strengthen its competitiveness in the market.